2016
DOI: 10.1213/ane.0000000000001062
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Midazolam for Preventing Postoperative Nausea and Vomiting

Abstract: Perioperative administration of midazolam was effective in preventing PON, POV, and PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 29 publications
1
37
0
3
Order By: Relevance
“…One week after surgery, the quality of recovery was even higher showing that the patients were recovering from surgery (ERAS protocol) and were almost ready for discharge. Grant et al 12 Ahn et al 13 and Mijderwijk et al 27 described reduced PONV after perioperative administration of midazolam. These effects may improve the quality of recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One week after surgery, the quality of recovery was even higher showing that the patients were recovering from surgery (ERAS protocol) and were almost ready for discharge. Grant et al 12 Ahn et al 13 and Mijderwijk et al 27 described reduced PONV after perioperative administration of midazolam. These effects may improve the quality of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Moreover, premedication with midazolam lowers the incidence of PONV, which might contribute to a better postoperative experience for patients. 12,13 Nevertheless, whether midazolam improves the overall quality of postoperative recovery is unknown. 14 For example, in two trials, one in ambulatory surgery patients and the other in patients undergoing scheduled inpatient surgery, lorazepam had no beneficial effect on the quality of postoperative recovery and actually resulted in a slower reduction in anxiety and increased aggression after surgery.…”
Section: Résumémentioning
confidence: 99%
“…In the meta-analysis, midazolam premedication resulted in decreasing the incidence and the severity of PONV. [ 26 , 27 ] In our study, intravenous midazolam of 0.03 mg/kg was used in every patient before entering the operation room, which might decrease the incidence of PONV in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large number of RCTs revealed that various drugs prevent PONV [24,25]. Dexamethasone has been used as a preoperative preventive antiemetic for quite some time.…”
Section: Discussionmentioning
confidence: 99%